"I want to help my body": Acceptability of malaria chemoprevention among children with sickle cell anaemia and their caregivers in Malawi and Uganda. - Sarah Svege; Siri Lange; Bjarne Robberstad; Joseph Rujumba (PLOS Global Public Health)
Patients with sickle cell anaemia (SCA) are at risk of severe illness and death if infected by malaria, and lifelong prophylaxis is recommended to individuals in malaria endemic regions. Although its efficacy is declining due to parasite resistance, the antimalarial drug Sulphadoxine-Pyrimethamine (SP) is still given to patients with SCA in several countries of sub-Saharan Africa. A clinical trial was performed to compare SP with Dihydroartemisinin-Piperaquine (DP) for malaria chemoprevention in children with SCA in Uganda and Malawi. This paper describes a study on acceptability which was nested within the trial. To explore views on malaria chemoprevention and the proposed treatment regimens, 29 focus group discussions were conducted with children above 10 years of age with SCA and caregivers of children with SCA. The discussions were transcribed and translated to English before coding and reflexive thematic analysis. Participants from the DP arm reported a reduced number of sick events and hospital admissions while they were in the trial, and ranked DP above SP in terms of perceived effectiveness. Although concerns were raised about initial side effects, a high pill burden, and the unpleasant smell and taste of tablets, most participants were willing to continue long-term administration of DP due to its observed or experienced health benefits. Despite positive attitudes towards the use of weekly DP, monthly dosing was frequently suggested as a better option as it would lower the pill burden and expand the time interval between treatment courses. To mitigate transport costs and time spent away from school and work, most participants preferred a period of two months or longer between drug refill visits at the hospital. During routine care visits, counselling about the importance of accurate dosing and ongoing adherence should be provided to ensure sustainable and successful use of malaria chemoprevention among children with SCA.